Kidney transplant outcomes in children and adolescents with systemic lupus erythematosus. (23rd October 2021) - Mai, Katherine; Singer, Pamela; Fahmy, Ahmed E.; Teperman, Lewis W.; Molmenti, Ernesto P.; Grodstein, Elliot I.; Castellanos, Laura; Sethna, Christine B.
Abstract: Background: Literature supports equivalent kidney transplant outcomes in adults with systemic lupus erythematosus (SLE) compared with those without SLE. However, there are conflicting and scant data on kidney transplant outcomes, as well as controversy over optimal timing of transplantation, in children and adolescents with SLE. Methods: Analysis included kidney‐only transplant recipients aged 2–21 years from 2000 to 2017 enrolled in the Organ Procurement and Transplant Network (OPTN). The relationship between diagnosis (SLE n = 457, non‐SLE glomerular disease n = 4492, and non‐SLE non‐glomerular disease n = 5605) and transplant outcomes was evaluated. The association between dialysis time and outcomes was analyzed in the SLE group only. Results: In adjusted models, SLE had higher mortality compared with non‐SLE glomerular recipients (HR 1.24 CI 1.07–1.44) and non‐glomerular recipients (HR 1.42 CI 1.20–1.70). SLE was associated with higher graft failure compared with non‐SLE glomerular (HR 1.42 CI 1.20–1.69) and non‐glomerular disease (HR 1.67 CI 1.22–2.28). SLE had a higher risk of acute rejection at 1 year compared with non‐glomerular disease (HR 1.39 CI 1.03–1.88). There was a decreased risk of delayed graft function compared with non‐SLE glomerular disease (HR 0.54, CI 0.36–0.82). There were no significant associations between dialysis time and transplant outcomes in the SLE group. Conclusion: SLE in children and adolescents is associated with worse patient and graft survival compared with non‐SLE diagnoses. Outcomes in children and adolescents with SLE are not associated with dialysis time. Further studies are needed to assess implications of potential earlier transplantation and shorter time on dialysis prior to transplantation.